Outbreak of IncX8 Plasmid–Mediated KPC-3–Producing Enterobacterales Infection, China - Chen, Lan; Ai, Wenxiu; Zhou, Ying; Wu, Chunyang; Guo, Yinjuan; Wu, Xiaocui; Wang, Bingjie; Rao, Lulin; Xu, Yanlei; Zhang, Jiao; Chen, Liang; Yu, Fangyou (Emerging infectious diseases, 2022)
Carbapenem-resistant Enterobacterales (CRE) infection is highly endemic in China; Klebsiella pneumoniae carbapenemase (KPC) 2–producing CRE is the most common, whereas KPC-3–producing CRE is rare. We report an outbreak of KPC-3–producing Enterobacterales infection in China. During August 2020–June 2021, 25 blaKPC-3–positive Enterobacteriale isolates were detected from 24 patients in China. Whole-genome sequencing analysis revealed that the blaKPC-3 genes were harbored by IncX8 plasmids. The outbreak involved clonal expansion of KPC-3–producing Serratia marcescens and transmission of blaKPC-3 plasmids across different species. The blaKPC-3 plasmids demonstrated high conjugation frequencies (10−3 to 10−4). A Galleria mellonella infection model showed that 2 sequence type 65 K2 K. pneumoniae strains containing blaKPC-3 plasmids were highly virulent. A ceftazidime/avibactam in vitro selection assay indicated that the KPC-3–producing strains can readily develop resistance. The spread of blaKPC-3–harboring IncX8 plasmids and these KPC-3 strains should be closely monitored in China and globally.